The Influence of Leadership, Interpersonal Communication, and School Culture through Work Ethic on Teachers' Professionalism at SMP Negeri 1 Kaloran - Nafi’ah, Hidayati; Raharjo, Tri Joko; Widiyanto, Widiyanto (Educational Management, 2025)
Teachers' professionalism is the result of the teacher's work performance or achievements based on their ability to manage the teaching and learning activities in the classroom. Many factors influence teachers' professionalism, including interpersonal communication, school culture, leadership, and work ethic. The objective of this research was to analyze the influence of interpersonal communication, school culture, and leadership on teachers' professionalism through work ethic as an intervening variable at SMPN 1 Kaloran. A quantitative approach was determined for this research. The population in this research consisted of 40 teachers, all from SMPN 1 Kaloran. The sampling technique used in this research was the total sampling method. The research instrument used was questionnaire, for which the validity and reliability have been tested beforehand. The data analysis for hypothesis testing used path analysis and Sobel test to find out the mediating variable. The findings showed that interpersonal communication, school culture, and leadership all have significant influence on work ethic. Interpersonal communication, school culture, and leadership also influenced teachers' professionalism mediated by work ethic. Based on these findings, teachers' professionalism can be improved through enhancements in interpersonal communication, school culture, leadership, and work ethic.